2007
DOI: 10.2527/jas.2006-752
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular fat deposition in principal muscles from twenty-four to thirty months of age using identical twins of Japanese Black steers

Abstract: The changes in i.m. fat deposition in the principal muscles [M. semitendinosus, M. semimembranosus, M. psoas major, M. latissimus dorsi, LM (7th to 8th and 10th to 11th thoracic vertebrae), and M. supraspinatus] from 24 to 30 mo of age were investigated using identical twins of Japanese Black steers. Four sets of identical twins of Japanese Black steers were used in this study. Animals were fattened from 10 to 24 or 30 mo of age for each pair of identical twins. Body weights of twin steers slaughtered at 24 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 15 publications
3
32
0
2
Order By: Relevance
“…There are several reports on changes in marbling score during the fattening period (Chung, 1997;Okumura et al, 2007Okumura et al, , 2012Yamazaki, 1981;Zembayashi et al, 1999). Zembayashi et al (1999) reported that intramuscular fat increased up to 36.7 months of age in Japanese Black cattle.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports on changes in marbling score during the fattening period (Chung, 1997;Okumura et al, 2007Okumura et al, , 2012Yamazaki, 1981;Zembayashi et al, 1999). Zembayashi et al (1999) reported that intramuscular fat increased up to 36.7 months of age in Japanese Black cattle.…”
Section: Discussionmentioning
confidence: 99%
“…May et al (1992) noted that most carcass grade traits increased linearly with days on feed, whereas most sensory panel variables and marbling increased curvilinearly. In contrast, Okumura et al (2007) reported that the additional fattening period of 6 mon from 24 to 30 mon of age in Japanese Black steers results in an increase in intramuscular fat which improves the quality grade.…”
Section: Introductionmentioning
confidence: 89%
“…The results of the present study indicate that Hanwoo steers have a great propensity for intramuscular fat deposition and that the process occurs until the later stage of the fattening period. Okumura et al (2007) reported that additional fattening period of 6 mon from 24 to 30 mon in Japanese Black steers resulted in an increase in intramuscular fat of m. longissimus. The percentages of carcasses achieving the greatest meat quality grade as assessed by the Japanese Meat Grading Association were 25% at 24 mon and 75% at 30 mon of age.…”
Section: Carcass Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Untuk meningkatkan produktivitas dan Departemen Ilmu Produksi dan Teknologi Peternakan, Fakultas Peternakan, Institut Pertanian Bogor, Kampus IPB Darmaga, Bogor 16680. * Penulis Korespondensi: E-mail: rd_priyanto@gmail.com kualitas sapi lokal dapat dilakukan dengan manipulasi pakan yang diberikan (Okumura et al 2007).…”
Section: Pendahuluanunclassified